Cutibacterium acnes Infection Induces Type I Interferon Synthesis Through the cGAS-STING Pathway - Fischer, Katrin; Tschismarov, Roland; Pilz, Andreas; Straubinger, Susy; Carotta, Sebastian; McDowell, Andrew; Decker, Thomas (Frontiers in Immunology, 2020)
Cutibacterium (previously Propionibacterium) acnes is an anaerobic, Gram-positive commensal of the human body. The bacterium has been associated with a variety of diseases, including acne vulgaris, prosthetic joint infections, prostate cancer and sarcoidosis. The accumulation of C. acnes in diseases such as acne and prostate cancer has been shown to correlate with enhanced inflammation. While the C. acnes-induced proinflammatory axis, via NF-κB and MAPK signaling and inflammasome activation, has been investigated over the last few decades, the potential role of C. acnes in triggering the type I interferon (IFN-I) pathway has not been addressed. Our results show that C. acnes induces the IFN-I signaling axis in human macrophages by triggering the cGAS-STING pathway. In addition, IFN-I signaling induced by C. acnes strongly depends on the adapter protein TRIF in a non-canonical manner; these signaling events occurred in the absence of any detectable intracellular replication of the bacterium. Collectively, our results provide important insight into C. acnes-induced intracellular signaling cascades in human macrophages and suggest IFN-I as a factor in the etiology of C. acnes-induced diseases. This knowledge may be valuable for developing novel therapies targeting C. acnes in diseases where the accumulation of the bacterium leads to an inflammatory pathology.